1981
DOI: 10.1002/1097-0142(19810515)47:10<2327::aid-cncr2820471003>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Searches for ultimate chemical carcinogens and their reactions with cellular macromolecules

Abstract: Studies on a variety of chemical carcinogens have demonstrated that their ultimate reactive and carcinogenic forms are strong electrophiles. Some carcinogens, such as alkylating agents, are in their ultimate forms as administered, but most require metabolism to these active derivatives. The ultimate carcinogens react, usually non-enzymatically, with nucleophilic constituents in vivo. Of particular interest in regard to their possible importance in carcinogenesis have been the covalent interactions of these ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
275
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 696 publications
(280 citation statements)
references
References 90 publications
2
275
0
2
Order By: Relevance
“…Apart from the potential value of the nasal epithelial cells for the prediction of cancer risk of the respiratory tract, 16,27 the use of nasal epithelia may allow mechanistic studies of various carcinogens, including those contained in tobacco smoke, 16,39 industrial air pollution, [20][21][22]28 and hair-dyeing. 49 Additionally, the patterns of Phase I enzymes that have an important role in the production of ROS during the metabolism of a number of carcinogens 50 are qualitatively different in the respiratory tract than in other tissues. 51 As previously mentioned, the levels of M 1 dG adducts were measured in the nasal epithelia to investigate the molecular mechanisms in the target site for FA-induced nasal carcinogenesis, since the formation of DNA damage in this region reflects the genotoxic action of FA as well as the actions of mediators released from the nasal epithelial cells following the inhalation of this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the potential value of the nasal epithelial cells for the prediction of cancer risk of the respiratory tract, 16,27 the use of nasal epithelia may allow mechanistic studies of various carcinogens, including those contained in tobacco smoke, 16,39 industrial air pollution, [20][21][22]28 and hair-dyeing. 49 Additionally, the patterns of Phase I enzymes that have an important role in the production of ROS during the metabolism of a number of carcinogens 50 are qualitatively different in the respiratory tract than in other tissues. 51 As previously mentioned, the levels of M 1 dG adducts were measured in the nasal epithelia to investigate the molecular mechanisms in the target site for FA-induced nasal carcinogenesis, since the formation of DNA damage in this region reflects the genotoxic action of FA as well as the actions of mediators released from the nasal epithelial cells following the inhalation of this compound.…”
Section: Discussionmentioning
confidence: 99%
“…PAH are ubiquitous environmental contaminants that result from incomplete combustion processes and are known carcinogens [8]. PAH are thought to exert their carcinogenic properties through their ability to form PAH-DNA adducts [9][10][11]. Both casecontrol [12] and cohort [13] studies have found that most jobs associated with occupational PAH exposure have the potential for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among molecular targets of xenobiotics, interest has been focused on DNA, since DNA-xenobiotic binding is considered to be a critical step that may initiate mutagenesis and carcinogenesis (Miller and Miller, 1981). Xenobiotics may interact with DNA either directly or after transformation by metabolizing enzymes into reactive species that react with DNA forming DNA addition products (DNA adducts).…”
Section: Introductionmentioning
confidence: 99%